Answer:
i dont know
Step-by-step explanation:
Y = 7
Explication pas à pas:
x est -3 donc -3 et connectez le x.
Y = -1 / 3 (-3) +5.
Y = 1 + 5
Y = 7
Start with assigning each person with a variable to represent their height
Ebi: e
Jose: j
Derell: d
Asami: a
Ebi'd height was 2.5 cm greater than Jose's height
j + 2.5 = e
Jose's height was 3.1 cm greater than Derell's
d + 3.1 = j
Derell's height is 0.4 cm less than Asami's height
a - 0.4 = d
Ebi is 162.5 cm tall
e = 162.5
So, plug in 162.5 into any of the above equations were there is a variable of e
j + 2.5 = e
j + 2.5 = 162.5
Subtract 2.5 from both sides of the equation
j = 160 cm
Jose's height is 160 cm
Now, plug in 160 into any of the above equations where there is a j
d + 3.1 = j
d + 3.1 = 160
Subtract 3.1 from both sides of the equation
d = 156.9 cm
Derell's height 156.9 cm
so, plug in 156.9 into any of the above equations where there is a d
a - 0.4 = d
a - 0.4 = 156.9
Add 0.4 on both sides of the equation
a = 157.3 cm
Asami's height is 157.3 cm